The Use of POCUS to Manage ICU Patients With COVID‐19. (11th November 2020) - Schrift, David; Barron, Keith; Arya, Rohan; Choe, Carol
Abstract : Since the advent of SARS‐CoV‐2, the virus that causes COVID‐19, clinicians have had to modify how they provide high‐value care while mitigating the risk of viral spread. Routine imaging studies have been discouraged due to elevated transmission risk. Patients who have been diagnosed with COVID‐19 often have a protracted hospital course with progression of disease. Given the need for close follow‐up of patients, we recommend the use of ultrasonography, particularly point‐of‐care ultrasound (POCUS), to manage patients with COVID‐19 through their entire ICU course. POCUS will allow a clinician to evaluate and monitor cardiac and pulmonary function, as well as evaluate for thromboembolic disease, place an endotracheal tube, confirm central venous catheter placement, and rule out a pneumothorax. If a patient improves sufficiently to perform weaning trials, POCUS can also help evaluate readiness for ventilator liberation.